Dampak Keberadaan Wisata Renzo Edu Park Terhadap Peningkatan Pendapatan dan Perekonomian Warga Desa Sekarwangi Kecamatan Cibadak Kabupaten Sukabumi - Istanti, Enny (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The role of tourism is expected to have a major impact on national development. The stages of implementing this community service, through a qualitative descriptive approach, where this community service is carried out to explain a more detailed picture of a symptom or phenomenon by looking at the object, namely the impact of Renzo Edu park tourist attractions on increasing income and economy of residents of Sekarwangi Village, Cibadak District, Sukabumi Regency. Of the 20 respondents of Sekarwangi village community who were correspondent in service interview activities in the income range of Rp. 500,000 – Rp. 1,000,000 before the existence of Renzo park there were as many as 8 respondents or about 40% of all respondents, while after the construction of Renzo park there were 4 respondents which means that in this range there was a decline. Income range of Rp. 1,000,000 – Rp. 1,500,000 before the existence of Renzo park there were 7 respondents or around 35%, while after the construction of Renzo park there were 6 respondents or around 30% which means it has decreased. For income of Rp. 1,500,000 – Rp. 2,000,000 before the existence of Renzo park there were 5 respondents or about 25% of all respondents, while after the construction of Renzo park there were 10 respondents or about 50% of all respondents which means that in this range has increased